A new genus and new species of pagurid hermit crab (Crustacea: Decapoda: Anomura: Paguroidea) from a submarine cave in Kume Island, Ryukyu Islands - Komai, Tomoyuki; Osawa, Masayuki (Zootaxa, 2012)
A new genus and new species of pagurid hermit crab, Kumepagurus cavernicolus, is described on the basis of a singlemale specimen collected from a submarine cave in Kume Island, Ryukyu Islands, at a depth of 38 m. The new genus su-perficially resembles Pylopaguropsis Alcock, 1905, in having13 pairs of biserial phyllobranchiae, the operculate rightchela and the possession of two terminal spines on the fixed finger of the left cheliped, but it is unique in the combination of 13 pairs of biserial gills and the presence of male sexual tubes.